Survey of West Nile virus infection in wildlife species in the Orinoquia region of Colombia - Nubia E. Matta; Felipe Andrés Gaitán-Albarracín; Gustavo Andrés Fuentes-Rodríguez; Óscar Andrés Rodríguez-Fandiño; Iván F. Calixto-Botía; Lady Johana Correa-Higuera (Frontiers in Microbiology)
Studies focused on the epidemiological surveillance of arboviruses that cause potentially zoonotic diseases, such as dengue, Zika, or emerging viruses like West Nile virus (WNV), are critical due to their significant impact on public health. Although research on these infectious agents is increasing in Colombia, regions remain where the presence of zoonotic agents is still unknown. To address this knowledge gap, the present study aimed to investigate the current status of WNV circulation in wildlife in two municipalities of the department of Casanare (El Yopal and Paz de Ariporo) from the Colombian region of Orinoquia. Since the arrival of WNV in Colombia, reported in 2004, its detection has typically relied on antibody screening using ELISA. While informative, this technique needs to offer a sufficiently precise time frame to confirm active virus circulation. We employed a molecular approach to overcome this limitation, detecting WNV using qPCR, which provides greater specificity and a narrower time window. A total of 2,553 swab samples were collected from a broad sampling covering 142 birds, 19 mammals, and eight reptile species during 2023 and 2024 across four sampling events conducted during both the dry and wet seasons. The sampling included species with ecological or symbolic value to the region and those with economic importance, such as species used for human consumption (bushmeat). No evidence of WNV was detected in the evaluated species, indicating that these species were not infected with the virus during the sampling periods or that viral loads were below the detection threshold. Our results underscore the importance of further studies, including complementary diagnostic methods, such as antibody detection, to better understand the broader temporal infections and provide a more complete understanding of virus circulation.